2017
DOI: 10.1002/cpp.2116
|View full text |Cite
|
Sign up to set email alerts
|

Ambivalence and guilt feelings: Two relevant variables for understanding caregivers' depressive symptomatology

Abstract: Providing care for a relative with dementia is considered to be a chronic stressor that has been linked to negative mental health consequences for caregivers. A theoretical model was developed and tested to assess the degree to which ambivalence and guilt feelings contribute to caregivers' depressive symptomatology. Participants included 212 dementia family caregivers. In addition to ambivalence and guilt feelings, sociodemographic characteristics, behavioural and psychological symptoms of dementia, and depres… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
48
0
4

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 50 publications
(58 citation statements)
references
References 43 publications
6
48
0
4
Order By: Relevance
“…This is a new finding in the existing literature on intergenerational ambivalence. One earlier small-scale study found an effect of ambivalence on guilt as well but without controlling for the main effects of negative and positive feelings (Losada et al, 2018).…”
Section: Resultsmentioning
confidence: 84%
See 3 more Smart Citations
“…This is a new finding in the existing literature on intergenerational ambivalence. One earlier small-scale study found an effect of ambivalence on guilt as well but without controlling for the main effects of negative and positive feelings (Losada et al, 2018).…”
Section: Resultsmentioning
confidence: 84%
“…In so far as guilt reduces well-being, it may also be relevant in understanding the presumed effect of intergenerational ambivalence on well-being. People who have conflicting emotions about their parents or children may have lower emotional well-being in part because they feel guilty about having these feelings (Losada et al 2018).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…There is also research on the guilt problem that some working mothers experience when combining a demanding professional job with the raising of their children (Guendouzi 2006;Henderson et al 2016). Some studies have examined the guilt that adult children feel toward their ageing and ill parents (Boll and Filipp 2002;Losada et al 2018). A recent study showed that adult children's feelings of guilt toward their mother are associated with feelings of ambivalence, with imbalances in support exchange, and with norms of filial responsibility (Kalmijn 2018).…”
Section: Introductionmentioning
confidence: 99%